Respon Pemerintah Daerah Atas Kebijakan Moratorium CPNS Terhadap Penataan Kelembagaan (Studi Kasus di Pemerintah Kabupaten Bantul 2011- 2014) - Rochma Bertiana; Dyah Mutiarin (Journal of Governance and Public Policy, 2015)
The problem in bureaucracy like bigness and inefficiency with huge organizational structure by large number ofemployees caused high expenditures. Moratorium on civil service recruitment policy that aims to suppress the growthpercentage of employees as well as pressing the personnel expenditure. Local Government Response for moratoriumon civil service recruitment policy, in this study was measured by parameters, 1). personnel expenditure budget; 2)Estimated Receipts civil servants;and 3) Workload. A high percentage of personnel expenditure is influenced by thenumber of civil servants, the number of certified teachers. To suppress the percentage by responses with completlymoratorium 1) The aspect of personnel arrangements. The existence of the moratorium, push Bantul Municipality tooptimize existing human resources. Implementation through the map position, and workload analysis, and 2) theaspect of institutional arrangements .Bantul Municipality Response in this aspect by preparation of a grand design inthe form of streamlining the organizational structure. B) based on the finding, the specific result showed the model ofinstitutional arrangement is implemented the business process models. This model emphasizes the effectiveness andefficiency of organizational processes. This model have the organizational structure with the same organizationalstructure in any organization. the difference is in the core output.